ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM MEMILIH WARUNG MAKAN SOTO DI KOTA SURAKARTA - Priyono, Edi; Retina, Ketty January; Nugroho, Totok Susilo Pamuji (STIE Atma Bhakti, 2024)
This research aims to find out and analyze whether product, price, location,service, facilities, advertising, atmosphere and word of mouth factors influence consumers in choosing soto food stalls in Surakarta City. The population used in this research was all consumers of soto food stalls in Surakarta City. The sampling technique used was Accidental Sampling, namely consumers who coincidentally met the researcher and were suitable as data sources totaling 100 people. This research is survey research using a quantitative approach. Data collection techniques use questionnaires and literature study. The data analysis technique used is multiple regression analysis and descriptive methods. The research results show that product, location, service, facilities, advertising, atmosphere and word of mouth have a positive and significant effect on purchasing decisions. Meanwhile, price has a negative and significant effect on purchasing decisions. Based on the results of the product determination coefficient, price, location, service, facilities, advertising, atmosphere and word of mouth explain 85.9% of the variation in purchasing decisions and 14.1% of purchasing decisions are explained by other variables not examined in this research. Keywords: Product, Price, Location, Service, Facilities, Advertising, Atmosphere, Word of Mouth and Purchasing Decisions